Formação de redes sociais e inovação : um estudo no Centro Incubador Tecnológico - CIT/FUNDETEC - Pereira, Jaiane Aparecida (2011)
Social network have gained a prominent place in development processes of innovation, which in turn came to be seen as a key to the survival of organizations. To understand how social networks can influence innovation, an alternative is study the social networks through the tieformation and evolution of the enterprises. Thus, the objective of this study is analyze how the formation and evolution processes of social network influenced the innovation of the four incubated enterprises of the Centro Incubador Tecnológico CIT/FUNDETEC since the foundation until 2011. To achieve the proposed objective, we made a descriptive qualitative study, using a multiple-case study, with longitudinal cut. We made two data collection in a period of six months, through semi-structured interview with managers of the incubated enterprises. Data analysis was chosen for content analysis using the software Atlas.ti. Among the results, demonstrates the importance of networks in both, formation and evolution of the enterprises, providing resources and information that assist in creation and development of innovation. The study also shows that incubator is more active in early years of the enterprises, each year the incubated depends less than incubator, being more closely to the market.